A study of neuroprotective effect stereospecificity of dipeptide mimetic of the Brain-derived neurotrophic factor GSB-106 on the model oxidative stress in the culture hippocampal cell line HT-22 - I. O. Logvinov; A. V. Tarasiuk; P. I. Antipov; T. A. Antipova (Фармакокинетика и Фармакодинамика)
In the present work, the neuroprotective effect stereospecificity of dimeric dipeptide mimetic of the 4th loop of BDNF-GSB-106 is studied. Activity of its diastereomers GT-106DL (hexamethylenediamide bis-monosuccinyl-D-seryl-L-lysine) and GT-106LD (hexamethylenediamide bis-monosuccinyl-L-seryl-D-lysine) in hippocampal HT-22 cells under conditions of oxidative stress is for this purpose studied. Both diastereomers were inactive. Thus, the obtained data indicate dependence of effect on the configuration of amino acid residues in the structure of GSB-106.